2003
DOI: 10.1029/2001jb001708
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation of the central Wasatch Mountains, Utah: 1. Patterns and timing of exhumation deduced from low‐temperature thermochronology data

Abstract: [1] The Wasatch Mountains are often cited as an example of normal fault growth and footwall flexure. They represent a tilted footwall at the edge of the Basin and Range extensional province, a major rift basin. Thus understanding the detailed spatial and elevation changes in coupled thermochronometer data, and how these changes can be interpreted, may aid in the analysis of thermochronometer data from other extensional regions around the world. We present a dense data set from the Cottonwood Intrusive Belt (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 53 publications
1
80
0
Order By: Relevance
“…The spatial distribution of the AFT ages indicates that the exhumation is greatest at the EHSF, and lessens away from the EHSF. Previous studies have demonstrated that in extensional tectonic regimes, most exhumation occurs in the footwalls of normal-fault bounded ranges, and results in the upward lateral advection of mass and heat in the footwall [26][27][28][29][30]. Therefore, the spatial variation of exhumation may reflect a component of tilt related to the normal faulting of the EHSF.…”
Section: Apatite Fission Track Results and Interpretationsmentioning
confidence: 94%
“…The spatial distribution of the AFT ages indicates that the exhumation is greatest at the EHSF, and lessens away from the EHSF. Previous studies have demonstrated that in extensional tectonic regimes, most exhumation occurs in the footwalls of normal-fault bounded ranges, and results in the upward lateral advection of mass and heat in the footwall [26][27][28][29][30]. Therefore, the spatial variation of exhumation may reflect a component of tilt related to the normal faulting of the EHSF.…”
Section: Apatite Fission Track Results and Interpretationsmentioning
confidence: 94%
“…These methods are able to record processes that affect the upper 2-6 km of the crust, depending on the geothermal gradients. Many studies have successfully identified patterns of cooling ages across a region that could be interpreted with respect to tectonics, erosion, landscape evolution, and climate (e.g., Armstrong et al, 2003;Reiners et al, 2007;Huntington et al, 2007;Barnes et al, 2012).…”
Section: Thermochronologymentioning
confidence: 99%
“…Since the modern resurgence of (U-Th)/He dating (Zeitler et al, 1987;Farley et al, 1996;Wolf et al, 1996), numerous studies have used (U-Th)/He thermochronometry to study a wide range of geomorphic and tectonic processes (House et al, 1998;Reiners et al, 2000;Stockli et al, 2000;House et al, 2001;Stockli et al, 2002;Armstrong et al, 2003;Ehlers et al, 2003;Reiners et al, 2003). More recent studies have exploited the relatively rapid ingrowth of He to date young volcanic deposits Aciego et al, 2003;Davidson et al, 2004;Min et al, 2005), and to understand diffusive loss of He associated with wildfires (Mitchell and Reiners, 2003) and shock metamorphism of meteroites (Min et al, 2004).…”
Section: Introductionmentioning
confidence: 97%